TECHNOLOGY INTEGRATION TO TEACH EFL YOUNG LEARNERS RECEPTIVE SKILLS IN BILINGUAL EDUCATION CONTEXT - Salsabila, Vina Aini (Tomorrow's Education Journal, 2024)
This study investigates the integration of technology in English as a Foreign Language (EFL) instruction for young learners within bilingual education contexts, focusing on receptive skills development. Through qualitative research methods, including interviews and document analysis, the study examines the impact of digital tools, such as LearningApps, on reading and listening skills acquisition. Findings reveal the transformative potential of technology integration in creating dynamic and engaging learning environments that cater to the diverse needs of digitally-native learners. While challenges such as connectivity issues persist, educators demonstrate resilience and creativity in overcoming obstacles. The study contributes to the existing literature by addressing the gap in research on technology integration in bilingual education settings and offering practical insights for educators and policymakers. Ultimately, the findings emphasize the importance of adapting pedagogical practices to harness the full potential of technology and empower students to thrive in an interconnected, technologically-driven world.